Analisis Perbedaan Harga Saham Perusahaan Sebelum Dan Sesudah Akuisisi (Studi Empiris Pada Perusahaan Yang Terdaftar Di BEI Periode 2013 – 2017) - Rizka Dyah Resvika Sari; M. Agus Salim; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study was to determine the analysis of differences in company stock prices before and after the acquisition of companies listed on the IDX in the period 2013-2017. This research is a type of quantitative research. The analysis used is seen from the stock price 1 day before the acquisition and the stock price 20 days after the acquisition. to distinguish stock prices before and after the acquisition this study uses the Paired sample T-test. The sampling technique used purposive sampling technique that is the sampling technique based on certain criteria obtained 36 companies from 44 companies as a population.The results of this study indicate that there is no difference in the company's stock price before and after the acquisition in companies listed on the IDX for the period 2013-2017. Based on the results of the research obtained it is advisable for companies to be careful in making acquisitions so that later can benefit the company and its shareholders. Keywords: Stock Price and acquisition